Analysis of critical thinking: potential variable differences between Malaysia and Indonesia - Mujanah, Siti; Ratnawati, Tri; Sumiati, Sumiati; Mohd, Rohani; Adha Hafid, Nor Intan (Technium Social Sciences Journal, 2023)
This research aimed to analyze factors that can influence the critical thinking of Indonesian and Malaysian to meet the competitive needs in the global market faced by college graduates. The population of this study were the students from several universities which were 116 from Malaysia and 175 from Indonesia. This research used a quantitative approach to analyze data to test hypotheses. Descriptive explanatory research methode used by finding the cause of the emergence of students’ critical thinking With this research, The data were collected using the survey method, which is a questionnaire as an instrument for gathering data. The findings indicate that factors that determine on Critical thinking of Indonesian and Malaysian were educational factors and personal factors. However, family factor and healthy food do not affect them substantially. Interestingly, in terms of education and family conditions, there were differences between Indonesian and Malaysian respondents, and Indonesian respondents' conditions are more favorable than those of Malaysians. Furthermore, students' factors and healthy food have significant differences. In this respect, Malaysian respondents show higher results than Indonesian respondents.